Effect of secondhand smoke exposure on lung function among non-smoking population - C., Aravind; B., Ragul; ., Monisha (International Journal of Advances in Medicine, 2019)
Background: Secondhand Smoke (SHS) exposure is known to be associated with various cardiovascular and respiratory problems but its effect on pulmonary function remains unexplored. This study was done to evaluate the effect of Secondhand Smoke (SHS) exposure on lung function among non-smoking population. Methods: This cross-sectional study was conducted in Bahour, Pondicherry from 2017-2018. 350 participants, age 40 year and older, with no respiratory symptoms or prior lung diseases were included in this study. Both self-reported history and measurement of urinary cotinine level were used to evaluate the smoking status. Spirometry data, including FVC and FEV1 were used to assess lung function. Diverse variables between groups were compared using T- test and Chi-square test. Analysis of covariance (ANCOVA) adjusted for age, height, alcohol consumption, and level of exercise was used to see any statistical differences in lung function parameters between non-SHS exposed and SHS-exposed groups. Results: Among 350 non-smokers, 120 were SHS-exposed. The urinary cotinine levels clearly distinguished SHS exposure, and the mean urinary cotinine levels were 7±0.3 and 11±0.4 in non-SHS exposed group vs SHS-exposed group, respectively. However, both groups had no significant difference in lung function and was found normal. Conclusions: SHS exposure urinary cotinine is a valuable marker.